Distributed adaptive control for distance-based formation and flocking control of multi-agent systems - Zou, Ying (2020)
In this study, a distributed adaptive control strategy for distance-based formation and flocking control of multi-agent system with parametric uncertainty is proposed. A 3-agent leader-first-follower system is considered first. The agents are supposed to have non-identical dynamics, whereas with similar structure. By introducing two new variables that involve distance error and velocity error and utilising them in the controller design, global convergence of all agents to the desired formation and to the velocity of the leader is established. Finally, the three-agent case is inductively extended to N-agent case. The stability and the effectiveness of the proposed control strategy are analysed in theory and demonstrated through simulation results, respectively.